ISEES MODEL: MODEL OF HOSPITAL SERVICE BASED ON INTERNAL AND EXTERNAL SERVICE QUALITY - Basuki Rachmat; Trisa Indrawati (Journal of Economics, Business, and Accountancy Ventura, 2012)
The research attempts to investigate public hospital service model and test the effect of theinternal and external service quality on employee satisfaction, employee satisfaction on theexternal service quality, external service quality on customer satisfaction, and customer loyalty.The research was conducted through questionnaires to 31 hospitals in Surabaya with1155 respondents. Validity and reliability are used to test the research instruments and researchhypotheses were tested by linear regression analysis. The results show there is a significantand positive effect of internal service quality on the employee satisfaction. There isalso a significant effect of internal service quality on external service quality. But, it alsoshows there is no significant effect of employee satisfaction on external service quality.Again, there is a significant and positive effect of external service quality on customer satisfaction,a significant and positive effect of customer satisfaction on customer loyalty.